PENGARUH LINGKUNGAN KERJA FISIK TERHADAP KEPUASAN KERJA PEGAWAI PADA DINAS PERPUSTAKAAN KOTA BIMA - Kurniati, Titi; Jaenab, Jaenab (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2020)
This study aims to find out how much influence the Physical Work Environment on Employee Job Satisfacion (Study of the Bima City Library Departement employees). While the formulation of the problem of this research is whether the Work Environment affects the Employee Job Satisfacion (Study of the Bima City library staff). The research instrument used a questionnaire. The type of researchÂ used Associative, this study was conducted at the Bima City Library Office, the population in this study was a total of 43 employees and the sample used in this study amounted to 30 employees using purposive sampling technique (sampling based on criteria). Data analysis used is a simple linear regression analysis using the equation, namely: Y = a + bx. The results of the initial analysis show that the indicators used are valid for measuring existing variables. The result of subsequent analyzes show that the Physical Work Environment variable influences the regression coefficient of 0.752Keywords: Physical Work Environment, Employee Job Satisfacion